Central Versus Extraventricular Neurocytoma in Children: A Clinicopathologic Comparison and Review of the Literature. Issue 6 (August 2016) - Zacharoulis, Stergios; Morales La Madrid, Andres; Bandopadhayay, Pratiti; Chi, Susan N.; Manley, Peter; Ullrich, Nicole N.J.; Marcus, Karen; Goumnerova, Liliana; Scott, Robert M.; Proctor, Mark; Young-Poussaint, Tina; De Girolami, Umberto; et al.
Abstract : Background: Central neurocytomas (CN) are rare pediatric CNS tumors most often with a benign clinical course. Occasionally, these tumors occur outside the ventricles and are called extraventricular neurocytomas (EVN). We present a retrospective institutional analysis of children with neurocytoma with prolonged follow-up. Procedure: Twelve patients were diagnosed with neurocytoma at our institution between 1993 and 2004. Results: Six patients were male and the median age at diagnosis was 12 years (1.5 to 16 y). Seven patients had CN and 5 had EVN. Presenting symptoms included headaches (67%), vomiting (50%), nausea (33%), seizures (33%), and mental status changes (25%). Obstructive hydrocephalus was present at diagnosis in 42% of the cases. Younger age and seizures were more common in patients with EVN. Gross total resection (GTR) was achieved in 42% (5/12) of the patients. Patients with GTR received no adjuvant therapy upfront; 1 patient subsequently had recurrence with leptomeningeal disease. Patients with subtotal resection received additional treatment: 1 underwent reoperation (GTR), 2 patients received focal radiation, 2 patients received adjuvant chemotherapy, and 2 patients received craniospinal irradiation followed by chemotherapy. The 20-year overall survival for this cohort was 83% with event free survival of 56%. Overall survival for CNs was 100%, versus 40% for EVN. Event free survival for CNs was 57% and 53% for the EVNs. An MIB-1 fraction >2% was associated with worse prognosis. Conclusions: Neurocytomas are rare brain tumors in children usually cured with GTR. Adjuvant focal radiation therapy and/or chemotherapy may improve disease control in cases with subtotal resection, but case-by-case analysis should be done. EVNs might be associated with worse outcome due to a higher proliferative index.